Implementation of Land and Building Tax Owned by Deceased Persons Reviewed from the Foundation of Sharia Economic Law - Asyhari, Shofarobbani (At-Tuhfah : Jurnal Studi Keislaman, 2025)
This study examines the implementation of land and building tax owned by deceased people, which is charged to the heirs. The purpose of this study is to determine and describe the imposition of tax on deceased people and the responsibility of their heirs according to the perspective of Sharia Economic Law. This study is a field research. Data collection techniques include observation, in-depth interviews, Forum Group Discussion, and content analysis. The theories used are the theories of Dharibah. The study results show that the problem of implementing a tax on deceased people in Sukorejo village according to The Regional Revenue Agency is caused by data that has not been updated. This can be resolved by updating and recording the latest data so that taxpayers for deceased people no longer appear as bills that must be borne by the new taxpayer (heir). According to the review of Sharia Economic Law, this case falls under the discussion of Dharibah, where the implementation of tax collection by the state can be justified as long as there is no element of oppression, and the state is in need.